The Life Impact Burn Recovery Evaluation (LIBRE) Profile: Historical Overview and Future Directions - Colleen M. Ryan; Jeffrey C. Schneider; Pengsheng Ni; Mary D. Slavin; Amy Acton; Ananya Vasudevan; Allan Sosa-Ebert; Lewis E. Kazis (European Burn Journal, 2025)
The Life Impact Burn Recovery Evaluation (LIBRE) Profile was developed to assess long-term social participation outcomes for adult burn survivors. Traditional clinical burn recovery outcomes focus on early physical complications and psychosocial issues, but there is a growing need for quantitative measures of long-term recovery that assess experiences deemed relevant to burn survivors. The LIBRE Profile, co-produced with input from burn survivors and clinicians and grounded in the World Health Organization’s International Classification of Functioning, Disability and Health (WHO-ICF) conceptual framework, addresses the measurement gap by focusing on six domains of social participation: social interactions, social activities, family and friends, work and employment, romantic relationships, and sexual relationships. The LIBRE Profile uses Item Response Theory (IRT) and computer adaptive tests (CAT) to minimize respondent burden while maintaining accuracy. Psychometric evaluations have validated the LIBRE Profile as a reliable and clinically useful tool that can help clinicians and burn survivors monitor recovery and inform personalized care. Future work includes LIBRE Profile development for pediatric populations, further international language translations, and the development of an APP for broader personal and clinical use. This paper provides a comprehensive overview of the LIBRE Profile’s development, psychometric foundations, and future directions, advocating for its adoption in clinical practice and burn survivor communities.